2021
DOI: 10.1016/j.powtec.2021.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Main powder physicochemical characteristics influencing their reconstitution behavior

Abstract: Thirty-six food powders corresponding to a wide range of physicochemical characteristics (bulk and surface chemical composition, median particle size, span, water activity) and manufacturing processes (grinding, freeze-drying, spray-drying, crystallization) were investigated for their reconstitutability. Their reconstitution profiles were acquired by conductivity measurements and fitted with Hill model. Physicochemical characteristics of investigated powders were correlated to their wetting and reconstitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Wettability is the ability of powders to immerse without stirring [1]. Powder wettability is sensitive to several parameters like particle size: smaller particles generally induce poorer wettabilityPowder surface composition also affects the wetting time: an increase in the proportion of surface lipids is deleterious for powder wettability due to higher hydrophobicity [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Wettability is the ability of powders to immerse without stirring [1]. Powder wettability is sensitive to several parameters like particle size: smaller particles generally induce poorer wettabilityPowder surface composition also affects the wetting time: an increase in the proportion of surface lipids is deleterious for powder wettability due to higher hydrophobicity [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Porosity, defined as the void fraction in the flour sample, is closely related to the reconstitution process in water. A flour with a higher porosity has good wetting behavior, a phenomenon related to the replacement of the gaseous phase by water at the powder surface . The results showed that the pretreatments increased this parameter value compared to those of raw counterparts (Table ).…”
Section: Resultsmentioning
confidence: 96%
“…As for instant properties, the desirable characteristics of powdered products can be categorized into four dissolution parameters: wettability, sinkability, dispersibility, and solubility. These properties represent the steps involved in the reconstitution of powdered products [10,37,38]. Figure 3 presents dissolution properties and how to improve their characteristics.…”
Section: Instant Propertiesmentioning
confidence: 99%
“…Wettability is defined as the ability of a liquid to penetrate a porous agglomerate, replacing the gaseous phase with water on the surface of the powder. The efficiency of this process is affected by particle size (directly proportional) and the degree of polarity on the surface (hydrophilic compounds have greater wettability) [10,37]. To enhance wettability properties, one approach is the use of additives with surfactant or emulsifying Wettability is defined as the ability of a liquid to penetrate a porous agglomerate, replacing the gaseous phase with water on the surface of the powder.…”
Section: Instant Propertiesmentioning
confidence: 99%
See 1 more Smart Citation